Emergency management of adrenal insufficiency in children: advocating for treatment options in outpatient and field settings. (28th February 2019) - Miller, Bradley S; Spencer, Sandra P; Geffner, Mitchell E; Gourgari, Evgenia; Lahoti, Amit; Kamboj, Manmohan K; Stanley, Takara L; Uli, Naveen K; Wicklow, Brandy A; Sarafoglou, Kyriakie
Abstract : Adrenal insufficiency (AI) remains a significant cause of morbidity and mortality in children with 1 in 200 episodes of adrenal crisis resulting in death. The goal of this working group of the Pediatric Endocrine Society Drug and Therapeutics Committee was to raise awareness on the importance of early recognition of AI, to advocate for the availability of hydrocortisone sodium succinate (HSS) on emergency medical service (EMS) ambulances or allow EMS personnel to administer patient's HSS home supply to avoid delay in administration of life-saving stress dosing, and to provide guidance on the emergency management of children in adrenal crisis. Currently, hydrocortisone, or an equivalent synthetic glucocorticoid, is not available on most ambulances for emergency stress dose administration by EMS personnel to a child in adrenal crisis. At the same time, many States have regulations preventing the use of patient's home HSS supply to be used to treat acute adrenal crisis. In children with known AI, parents and care providers must be made familiar with the administration of maintenance and stress dose glucocorticoid therapy to prevent adrenal crises. Patients with known AI and their families should be provided an Adrenal Insufficiency Action Plan, including stress hydrocortisone dose (both oral and intramuscular/intravenous) to be provided immediately to EMS providers and triage personnel in urgent care and emergency departments. Advocacy efforts to increase the availability of stress dose HSS during EMS transport care and add HSS to weight-based dosing tapes are highly encouraged.